دراسة حالة بمركز الضرائب بولاية الوادي إسهامات التدقيق المحاسبي في دعم الرقابة الجبائية - بروبة أشرف; الأشهب محمد أيمن; داودي أنور (جامعة الوادي University Of Eloued, 2025)
هدفت هذه الدراسة إلى إبراز إسهامات التدقيق المحاسبي في دعم فعالية الرقابة الجبائية، من خلال المزج بين المعالجة النظرية والتحليل التطبيقي. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، مدعومًا بدراسة حالة لمركز الضرائب بالوادي، كأداة لفهم الواقع الميداني لآليات الرقابة الجبائية ومدى تكاملها مع أدوات التدقيق المحاسبي، وتوصلت الدراسة إلى أن التدقيق المحاسبي يمثل أداة فعالة لتحسين جودة الرقابة الجبائية، من خلال تحليل المعطيات المالية وكشف الثغرات في التصريحات الضريبية، مما يسهم في تعزيز العدالة الجبائية وزيادة مردودية الإدارة الضريبية، كما أظهرت النتائج أهمية كفاءة الأعوان، دقة البيانات المحاسبية، والتنسيق بين مختلف الهياكل، إلى جانب الحاجة لتبسيط النصوص الجبائية وتوظيف الوسائل الرقمية الحديثة. This study aimed to highlight the contributions of accounting auditing in enhancing the effectiveness of tax control, by combining theoretical analysis with practical application. The study adopted a descriptive and analytical approach, supported by a case study of the Tax Center in El Oued, as a tool to understand the field reality of tax control mechanisms and the extent of their integration with auditing tools. The findings revealed that accounting auditing is an effective tool for improving the quality of tax control through the analysis of financial data and the identification of gaps in tax declarations. This contributes to promoting tax justice and increasing the efficiency of the tax administration. The results also highlighted the importance of staff competence, the accuracy of accounting data, and coordination among various structures, in addition to the need to simplify tax texts and adopt modern digital tools
Keywords: الرقابة الجبائية – التدقيق المحاسبي – الضرائب .; Tax control - Accounting audit - Taxes .